PROGRAM PENGEMBANGAN PROFESIONALITAS PETUGAS BIMBINGAN SEKOLAH : Studi Deskriptif-Analitis Dalam Rangka Pengembangan Kemampuan Profesional Petugas Bimbingan Sekolah Menengah Atas Negeri Di Padang Oleh Organisasi Profesi Bimbingan - A Muri Yusuf, - (1995)
Guidance and Counseling as an integral part of education, have contributed a lot to the students development. However, there are still so many factors to be considered and to be given more serius attention, such as a guidance staff which is more or less passive and tends to wait for his or her client to come asking for help; a guidance staff which has done so little efforts to be of much help for the students in their study, his or her activities are still insufficient and not yet well-coordinated and in many instances not purposeful enough to achieve the various goals of the school program. There is no significant difference between the achievements of those guidance staffs with special guidance and counseling background and those who have no guidance and counseling pre-service education background. These phenomena bring about so many problems that need immediate solutions to raake guidance and counseling program at schools more professional and more successful!. The present study was concentrated and aimed at the development and improvement of guidance personnel at Senior High School based on the analysis of the relation-ship between relevant factors, guidance staffs personal